Prediction, context, and competition in visual recognition. (27th February 2015) - Trapp, Sabrina; Bar, Moshe
Abstract : Perception is substantially facilitated by top‐down influences, typically seen as predictions. Here, we outline that the process is competitive in nature, in that sensory input initially activates multiple possible interpretations, or perceptual hypotheses, of its causes. This raises the question of how the selection of the correct interpretation from among those multiple hypotheses is achieved. We first review previous findings in support of such a competitive nature of perceptual processing, and then propose which neural regions might provide a platform for rising and using expectations to resolve this competition. Specifically, we propose that it is the rapid extraction and top‐down dissemination of a global context signal from the frontal cortices, particularly the orbitofrontal cortex, that affords the quick and reliable resolution of the initial competition among likely alternatives toward a singular percept.